(untitled) (Research, Society and Development, 2021)
In the context of the Coronavirus 2020-21 Pandemic, services mediated by Information and Communication Technologies are essential for various social sectors, especially for Education. The feasibility of conducting online classes and working remotely allow the maintenance of activities without the need for displacements or crowding. In this sense, this research aimed to analyze the perception of administrative technical servants of the Instituto do Noroeste Fluminense for Higher Education (INFES / UFF) with regard to the carrying out of activities originating in Information and Communication Technology and their daily lives during the remote work. This research is characterized as quantitative and descriptive, having used a questionnaire as a data collection instrument, made available via the WhatsApp group. The results obtained showed that the institution’s IT sector is of paramount importance for the good development of the work of administrative technicians, in person or remotely. Still, the strategic planning of this user’s sector, the proper functioning of its structure, as well as the implementation of tools to enable remote work during a pandemic, ensuring efficient support to users.